BOARD DIVERSITY, CORPORATE SOCIAL RESPONSIBILITY, AND FINANCIAL PERFORMANCE: AN EMPIRICAL STUDY ON CONSUMER NON-CYCLICAL FIRMS - Ainun Nizmah, Kemala; Nurul Innayah, Maulida; Purwidianti, Wida; Bagis, Fatmah (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
This study aimed to examine the effect of board diversity on financial performance of consumer non-cyclicals companies listed on the Indonesia Stock Exchange. This study also examined the mediating effect of Corporate Social Responsibility on the relationship between board diversity and financial performance which was limited in previous studies. The sampling technique used was purposive sampling which obtained 136 observations. The results showed that female directors, foreign directors, and directors with economic education have a negative effect on financial performance. Female directors and foreign directors have a positive effect on CSR, while directors with economic education have a negative effect on CSR. CSR has a positive effect on financial performance. However, based on the sobel test results, CSR is not able to mediate the relationship between board diversity on financial performance. This research has contributed for consumer non-cyclicals companies to consider the role of board diversity, because this research found that they are able to increase CSR disclosure and firm performance.